Modified energy efficient multi-level and spectrum aware unequal clustering with primary user classification in cognitive radio sensor networks - Subrahmanyam, Ch; Lakshmi, T.R. Vijaya; Kumar, K. Praveen; Naidu, M. Lakshmu; Sireesha, Majeti Venkata; Sujeetha, G. Spica (Edelweiss Applied Science and Technology, 2024)
The study has produced a cross-layered routing protocol, which was built as part of the research. This protocol uses an updated contention window technique and Particle Swarm Optimization (PSO) to construct consistent and energy-efficient network routing pathways. The protocol was established as a result of the study. The PSO algorithm takes into account a variety of metrics, including as the Traffic index, Average energy load, data success rate, and trust value, in order to successfully optimize routing patterns. These parameters are all calculated at the network layer. Contention windows at the MAC layer are constantly modified according to real-time measurements of contentions and average energy loads. This further improves the efficiency of communication by taking into account the data. The trustworthiness of a node is decided by taking into account not only the quality trust that is generated from the node’s Quality of Service (QoS), but also the group trust that is offered by neighbouring nodes. As a consequence of this procedure, detailed trust ratings are bestowed onto individual nodes; these ratings serve as a guide for selecting relay nodes. In addition, the study presents a dual authentication system, which incorporates advanced dual authentication (EnDA) methodologies and key management processes to strengthen data security and guarantee data integrity. In addition, Elliptical Curve Cryptography (ECC) and Diffie-Hellman key exchanges using bilinear maps have been employed to further strengthen the security of communications. According to the findings of the tests, the suggested protocol has impressive performance in terms of successfully establishing a secure key agreement while data is being sent and maintaining acceptable levels of energy usage.